2015
DOI: 10.1002/cbdv.201400404
|View full text |Cite
|
Sign up to set email alerts
|

4‐Cyano‐α‐methyl‐l‐phenylalanine as a Spectroscopic Marker for the Investigation of PeptaibioticMembrane Interactions

Abstract: Two analogs of the ten-amino acid residue, membrane-active lipopeptaibiotic trichogin GA IV, mono-labeled with 4-cyano-α-methyl-L-phenylalanine, a potentially useful fluorescence and IR absorption probe of the local microenvironment, were synthesized by the solid-phase methodology and conformationally characterized. The single modification was incorporated either at the N-terminus (position 1) or near the C-terminus (position 8) of the peptide main chain. In both cases, the replaced amino acid was the equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…These findings were confirmed by polarized ATR‐FTIR spectroscopy, which allows the average orientation of helical peptides inside lipid bilayers to be determined (Figure , Table ). For these studies, we employed an unlabeled trichogin analogue and two sequences labeled with para ‐cyano(αMe)phenylalanine (PheCN), which had previously been investigated by exploiting the PheCN fluorescence and IR signals, and had been demonstrated to insert into the membrane . Table shows the dichroic ratio ( R ) for the amide I band in the region between 1600 and 1700 cm −1 , the order parameter ( S ), and the angle formed by the helix axis with the bilayer normal α .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were confirmed by polarized ATR‐FTIR spectroscopy, which allows the average orientation of helical peptides inside lipid bilayers to be determined (Figure , Table ). For these studies, we employed an unlabeled trichogin analogue and two sequences labeled with para ‐cyano(αMe)phenylalanine (PheCN), which had previously been investigated by exploiting the PheCN fluorescence and IR signals, and had been demonstrated to insert into the membrane . Table shows the dichroic ratio ( R ) for the amide I band in the region between 1600 and 1700 cm −1 , the order parameter ( S ), and the angle formed by the helix axis with the bilayer normal α .…”
Section: Resultsmentioning
confidence: 99%
“…The para ‐fluorophenylalanine‐containing trichogin ([ 19 F‐Phe10]trichogin) and the p ‐cyano(αMe)phenylalanine (PheCN) trichogins were prepared as described in refs. and , respectively. Synthesis of trichogin GA IV‐OMe was described in ref.…”
Section: Methodsmentioning
confidence: 98%
“…In this moiety, key HMBC correlations from the proton at δ H =6.82 ppm (s, H‐2′) to two quaternary carbons at δ C =115.0 (s, C‐3′) and 116.8 ppm (s, C‐13′) (Figure 32 S in the Supporting Information) suggested that the substituent at C‐3’ was a cyano group (Figure ), which was biologically produced through the elimination of a water molecule of an oxime group. The infrared (IR) absorption bands at 2225 cm −1 confirmed the presence of the cyano group (Figure 35 S in the Supporting Information) . Considering the overall formula of 4 , an ester bond was determined to be between the oxime hydroxyl and C‐7′, as described in 3 .…”
Section: Resultsmentioning
confidence: 90%
“…Phe CN is an α‐amino acid with interesting IR absorption and emission (in the UV region) properties . Its IR absorption band is centered at approximately 2230–2240 cm −1 , that is, in a spectral region completely free of overlap with other bands.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it has been used as an environmental probe in studies of protein and peptide conformations and interactions. In particular, a few investigations reported the IR absorption properties of the Phe CN probe for peptides associated to bicelles or phospholipid membranes . However, a simplistic analysis of the band properties in terms of local electric field is not warranted, because of the additional dependence of the IR absorption peak on H‐bond formation, solvent dynamics, and other more complex electrostatic interactions .…”
Section: Introductionmentioning
confidence: 99%